PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DI DESA LALUMPE KECAMATAN MOTOLING KABUPATEN MINAHASA SELATAN - Merentek, Olivia; Pangkey, Masje Silija; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2018)
ABSTRACT : Public participation is as a form of the involvement of members of the community in alldevelopment which includes activities in the planning and implementation of development programs.Community participation in the form of participation is supporting success program given by thegovernment. Program Development programs village axis road in the village aims to public welfare is tomake access easier in doing their activity originally road conditions unfit for impassable winter hence inexpect participation of the community to resolve existing problems in the village.This study attempts to describe participation in rural development planning through musrenbangin lalumpe village motoling. Research method used is descriptive with a qualitative approach. But speakersthis study of them are village officials and villagers lalumpe. Data collection , reduction data, presentationof data, and the withdrawal of conculusion.The result showed that villagers lalumpe in motoling district minahasa selatan gave participationand support in development village road. Villagers lalumpe willing to give their participation in any activityconducted the participation in planning, participation in benefit, participation in evaluation. In this researchshows that public participation can be assessed good demonstrated by the role of the active in thedevelopment although it needs evaluation in development village road in order to resolve wellAdvice given in this research is that the program can be accomplished with coordination namelywith the community to the people support fully in the smooth development of village road.Keywords : Public Participation. Planning, Development